The Effect Of Work Environment, Integrity And Work Flexibility On Job Satisfaction With Competence As An Intervening Variable In Bank Indonesia Representative Office North Sumatera Province - Khairuddin; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
In any organization, human resources are very important in carrying out activities carried out by the organization, because human resources function as a stepping stone for the organization to achieve its business success goals. This study aims to determine the Influence of Work Environment, Integrity and Work Flexibility on Job Satisfaction with Competence as an Intervening Variable at the Representative Office of Bank Indonesia, North Sumatra Province. The results of this study are as follows: Work Flexibility has a positive and insignificant effect on Job Satisfaction with an original sample value of 0.095 and p values 0.316. Work Flexibility has a positive and significant effect on Competence with an original sample value of 0.427 and p values 0.000. Integrity has a positive and insignificant effect on job satisfaction with an original sample value of 0.085 and p values 0.365. Integrity has a positive and significant effect on competence with an original sample value of 0.347 and p values 0.002. Competence has a positive and significant effect on Job Satisfaction with an original sample value of 0.520 and p values of 0.026. Work Environment has a positive and insignificant effect on Job Satisfaction with a value of 0.108 p values 0.272. Work Environment has a positive and significant effect on Competence with an original sample value of 0.191 and p values 0.032. Work Flexibility has a positive and insignificant effect on Job Satisfaction through Competence with an original sample value of 0.222 and p values 0.052. Integrity has a positive and insignificant effect on Job Satisfaction through Competence with an original sample value of 0.181 and p values 0.058. Work Environment has a positive and insignificant effect on Job Satisfaction through Competence with an original sample value of 0.100 and p values 0.106.